Margaritaella gracilis gen. n. et sp. n. (Eucestoda: Proteocephalidea), a parasite of Callichthys callichthys (Pisces: Siluriformes) from the Paraná River basin, Argentina - Arredondo, Nathalia J; Gil de Pertierra, Alicia A (Folia parasitologica, 2012)
Margaritaella gracilis gen. n. et sp. n. (Proteocephalidea: Proteocephalinae) found in the intestine of Callichthys callichthys (Linnaeus) from the Paraná River basin is described. The new genus is placed in the Proteocephalinae because of the medullary position of the genital organs. It differs from all known genera included in the Proteocephalinae by the following combination of characters: 1) scolex with a conspicuous cluster of drop-shaped gland cells posterior to suckers; 2) strobila with a low number of proglottides, all much longer than wide; 3) testes arranged in one field, composed of two parallel rows of testes separated by the uterus; 4) ovary delicate, H-shaped, with branches slender and deeply folliculate at the edges, located at 25–35% from the posterior end; 5) uterus largely extended posterior to the ovary but not reaching the end of proglottis; and 6) vitelline follicles in two narrow lateral bands, largely extended posterior to the ovary. Scanning electron microscopy revealed three types of microtriches on the tegument surface: acicular and capiliform filitriches and gladiate spinitriches. The relative size of the ovary, a character recently used in the systematics of the proteocephalidean cestodes, was calculated for the new species and compared with other species of the group. M. gracilis is the first record of a proteocephalidean cestode parasitizing a callichthyid catfish.
Keywords: Catfishes; sumci; Cestoda; řeky; Animals; mikroskopie elektronová rastrovací; Argentina; Microscopy, Electron, Scanning; cestodózy; Rivers; zvířata; nemoci ryb; Cestode Infections; Fish Diseases